2013
DOI: 10.2527/jas.2012-5554
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for quantifying the behavioral activity of dairy cows in freestall barns1

Abstract: The objectives of this study were to 1) evaluate the validity of automated monitoring systems as assessment method for the behavioral activity of dairy cows compared with video recording, and 2) determine the sampling intervals required to obtain reliable estimates of the daily behavior. To determine lying, standing, and walking, 12 cows were equipped with automatic recording devices (IceTag = 12 cows, HOBO Pendant G = 5 cows), and their behavior was simultaneously recorded using a video recording system. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 24 publications
6
91
0
Order By: Relevance
“…Mattachini et al (2013) reported that just 30% of the walking events were correctly detected. This is mainly because the transition from standing to walking and vice versa is physically less distinctive than from the lying to the upright position (Trenel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mattachini et al (2013) reported that just 30% of the walking events were correctly detected. This is mainly because the transition from standing to walking and vice versa is physically less distinctive than from the lying to the upright position (Trenel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Mattachini et al (2013) concluded that sampling intervals ≤2 min are required to accurately measure aspects of lying behavior such as number of lying bouts per day. From the results of the current study, it remains unclear whether reduction of the sampling rate to 1 Hz might be possible without loss of important information mainly concerning the walking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…HOBO U12 Temp/RH/Light/External Data Logger (Onset Computer Corporation, Bourne, MA, USA) sensors were installed in every farm in two different positions in the barn and at the height of 2 m in accordance with Mattachini et al (2013) [29]. They were installed inside the barn to collect data about the environmental living conditions of dairy cows.…”
Section: Climatic Variablesmentioning
confidence: 99%
“…The HOBO Pendant sensor was mounted on the leg by means of tape and a plastic tough leg band in order to have the sensor positioned with the x-axis of the data logger perpendicular to the floor. The degree of vertical tilt of the x-and z-axis was used to quantify the behavior of the animal and, in particular, the standing or lying behavior [29].…”
Section: Monitoring Of Cows' Behaviormentioning
confidence: 99%
“…Behavior is an indicator of the well-being and health of dairy cows (BORCHERS et al, 2016). Cows exhibit different behavior when health problems or physiological conditions (e.g., estrus) develop (MATTACHINI et al, 2013). For instance, comparing with non-lamed cows, lamed cows spend more time lying and less time standing, perform fewer aggressive interactions and are less active.…”
Section: Introductionmentioning
confidence: 99%